Beyond birth-weight: Improved ascertainment of early growth predicts blood pressure in Peruvian adolescents - Sterling, Robie; Checkley, William; Gilman, Robert H; Cabrera, Lilia; Sterling, Charles R; Bern, Caryn; Miranda, J. Jaime (PeerJ PrePrints, 2014)
Background: Longitudinal investigations into the origins of adult essential hypertension have found elevated blood pressure in children to accurately track into adulthood, however the direct causes of essential hypertension in adolescence and adulthood remains unclear. Methods: Cohort study, we revisited 152 Peruvian adolescents from a birth cohort evaluated with monthly anthropometric measurements between 1995 and 1998, and obtained anthropometric and blood pressure measurements 11 to 14 years later. We used multivariable regression models to study the effects of infantile and childhood growth trends on blood pressure and central obesity in early adolescence. Results: In regression models adjusted for childhood growth, each 0.1 SD increase in weight for length from 0 to 5 months of age, and 1 SD increase from 6 to 30 months of age, predicted decreased adolescent systolic blood pressure by 1.3 mm Hg (95% CI -2.4 to -0.1) and 2.5 mm Hg (95% CI -4.9 to 0.0), and decreased waist circumference by 0.6 (95% CI -1.1 to 0.0) and 1.2 cm (95% CI -2.3 to -0.1) respectively. Growth in infancy and early childhood was not a significant predictor of adolescent waist-to-hip ratio. Conclusions: Rapid compensatory growth in early life has been posited to increase the risk of long-term cardiovascular morbidities such that nutritional interventions may do more harm than good. However, we found increased weight growth during infancy and early childhood to predict decreases in adolescent systolic blood pressure and central adiposity.
Keywords: Hypertension; developmental origins; obesity; lifecourse; Peru; cohort study